Climate Change and Water Dynamics in Rural Uganda - McKinney, Laura; Wright, Devin C. (MDPI AG, 2021)
The purpose of this case study is to examine the effects of climate change on agricultural life in rural Uganda. Based on primary data, the authors examine major themes related to climate change and disasters as conveyed by individuals in a small agricultural region in Eastern Uganda. Specifically, we focus on the effects of living in constant threat of flooding and landslides. Results show that water is a major source of loss for most people, ranging from crop loss to contaminated water. Findings also point to the chronic nature of dealing with water issues, as opposed to acute. Further, our results indicate that disasters are a great equalizer among affected populations, with only neighbors to depend on in the aftermath.
Keywords: climate change; water crises; Uganda; community sustainability; landslides